Web-Based New Building Point Information System in Tebo Regency: Sistem Informasi Titik Bangunan Baru Pada Kabupaten Tebo Berbasis Web - Winarti, Dwi; yusran; Tri Yuniko, Fauzi; Pratiwi, Tias; Nur Aisyah, Sinta; Destriani, Fika (Journal of Vocational Education and Information Technology (JVEIT), 2023)
Tebo Regency is one of the regencies in Jambi Province. This district is the result of expansion of the Bungo Tebo district. Tebo Regency has developed from year to year, from the economic, social, infrastructure and population sectors. This study discusses the data and location of new housing in Tebo Regency, especially in the village of Giri Purno. The method used by the author to design the system is the SDLC (System Development Life Cycle) methodology. The shape of this system is like a waterfall. The results of this website can be accessed by the wider community to find related information. The methodology used is waterfall, the design tool uses UML and Php Mysql.